If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(3y + -10) + -1y = -3(y + -5) Reorder the terms: -3(-10 + 3y) + -1y = -3(y + -5) (-10 * -3 + 3y * -3) + -1y = -3(y + -5) (30 + -9y) + -1y = -3(y + -5) Combine like terms: -9y + -1y = -10y 30 + -10y = -3(y + -5) Reorder the terms: 30 + -10y = -3(-5 + y) 30 + -10y = (-5 * -3 + y * -3) 30 + -10y = (15 + -3y) Solving 30 + -10y = 15 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 30 + -10y + 3y = 15 + -3y + 3y Combine like terms: -10y + 3y = -7y 30 + -7y = 15 + -3y + 3y Combine like terms: -3y + 3y = 0 30 + -7y = 15 + 0 30 + -7y = 15 Add '-30' to each side of the equation. 30 + -30 + -7y = 15 + -30 Combine like terms: 30 + -30 = 0 0 + -7y = 15 + -30 -7y = 15 + -30 Combine like terms: 15 + -30 = -15 -7y = -15 Divide each side by '-7'. y = 2.142857143 Simplifying y = 2.142857143
| -3(6y-9)-y=-4(y-4) | | 42x/83*59/14 | | 27/32/(-9/4) | | (42x/83)*(59/14) | | 27/32/-9/4 | | 4(x-25)=24x | | 1/6+8 | | 3x+24=48+10x-30 | | 37x+2=6(6x+6) | | 3x(x+4)=2(5-x) | | y-8*-1/6(x-1) | | -39=-18-r | | 2x-5x+4=x-3+7 | | 2x^2+40x-225=0 | | 9x-(6x+9)=9x-21 | | 15+x/5=10 | | -4=t-13 | | k+(-21)=-15 | | 4xy^2-y^3+3x^2=0 | | 21-[2+8y-3(y+4)]=-3(2y-5)-[9(y-1)-7y+11] | | 8w=6+16 | | 34(1/6/17) | | -24=x+2 | | 3m+4n=-14 | | 40y^6/5y^3 | | (2y+3)/(4y-1)=(3y-2)/(3y+2) | | 2y+4y-8x^2=6 | | 5x+40-6x=3-9x+5 | | 4(5+2x)=7(x-5) | | 7x-(2x-5)=20 | | 3n+5n=7(-7n) | | 2(1-5x)=-8 |